Unveil memories with the deconstruction of obelisks - Rahme, Anna Maria (Revista ARA, 2021)
This research aimed to examine the dismantling of the norms imposed in the memorials erected after the second half of the twentieth century, which at the same time destitute the hegemonic narratives in public spaces - such as those that govern the construction and implementation of obelisks - and, while deconstructing them, use the same attributes by inverting them and, therefore, introducing new concepts. Explored by James Edward Young, counter-monuments dispute the historical linearity, single discourse, spatial domination, activating the observer, previously passive, by the dynamic conditions of place and work.